Association between dietary inflammation index and albuminuria: results from the National Health and Nutrition Examination Survey - Ding, Ling; Guo, Haipeng; Zhang, Chao; Jiang, Bo; Zhang, Shuo; Zhang, Jian (Frontiers in Nutrition, 2024)
Background: The Dietary Inflammation Index (DII) is a tool for evaluating the potential for dietary inflammation, and inflammation is a major cause of exacerbation in chronic kidney disease. Our study aimed to investigate the relationship between DII and albuminuria.Methods: Data were obtained from the 2005-2018 National Health and Nutrition Examination Survey (NHANES) after excluding pregnant, minors, and missing data of urinary albumin-creatinine ratio (ACR), estimated glomerular filtration rate (eGFR), and DII were enrolled in our study. Albuminuria was defined as ACR > 30 mg/g. DII was calculated and divided into tertiles. After fully adjusted, multivariate logistic regression analysis and subgroup analysis were performed to investigate the association between DII and albuminuria.Results: A total of 22,607 participants including 2,803 (12.40%) with and 19,804 (87.60%) without albuminuria were enrolled in our study. The albuminuria increased with the increasing DII tertiles (Tertile 1: 10.81%; Tertile 2: 12.41%; Tertile 3:13.97%, P<0.001). After fully adjusting for covariates, multivariate logistic regression showed that the higher the DII, the greater the odds of albuminuria(OR = 1.19; 95% CI, 1.00 -1.41, P<0.001). Subgroup analysis and interaction test of participants found that the positive correlation between DII and albuminuria was not significantly related to gender, age, BMI, hypertension, diabetes, and eGFR (P for interaction>0.05).Elevated DII is associated with high odds of albuminuria. Further largescale prospective studies are still needed to analyze the role of DII in albuminuria.